Gambaran Sikap Keluarga Terhadap ODS (Orang Dengan Skizofrenia) Di Desa Kertajaya Kecamatan Cibatu Kabupaten Garut - Vina Nurdianasari; Hendrawati; Efri Widianti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
People with schizophrenia (PWS) certainly need a role of family as people closest. The relapse in people with schizophrenia is greatly influenced by family attitudes, at this time there are still many families incorrectly behaving like stay away, hostile, avoid and hates the patient on the grounds of shame eventually worsen the condition of PWS. The purpose of this study is to determine family attitudes towards PWS in Kertajaya Village, Cibatu Sub-District, Garut District.Research method used in this study is quantitative descriptive with a population of families who have PWS in Kertajaya Village, Cibatu Sub-District, Garut District. Samples are obtained using total sampling techniques with the total of 43 family members. The instrument used in this study is the Family Attitude Scale (FAS) questionnaire with the validity value (0.413-0.812) of r count ? 0.329. Reliability test with the value of 0.89. The results of this study show that in terms of the family attitude toward PWS, of 43 respondents, 22 family members (52.2%) perform attitude categorized as positive attitude and 21 (48,8%) negative. The family attitude included in positive category may be due to sufficient knowledge background, the role of good health workers. While the negative one may be due to exhaustion and disappointment because of the condition of PWS. This research results